Mergers and Acquisition in the Nigerian Banking industry - Ajani, Olukayode (2007)
Merger and Acquisition has become an increasingly common reality of the organizational life (Buono and Bowditch 1989). Although a lot of articles have been written about the monetary, management efficiency, shareholders wealth maximization and strategic aspects of M&A, not so many have written on the impact on the banking industry as regards to the financial and non-financial positive effects of the synergy amongst the various banks involved in the merger. Based on the peculiarity of the merger as it was not motivated by banks in a drive to seek efficiency by was as a result of a directive issued by the Central Bank of Nigeria with aimed at strengthening the financial capacity of the banks.